2021
DOI: 10.3390/vaccines9030288
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Post-Transplant Active Epstein-Barr Virus Infection and Lymphoproliferative Disease in Hematopoietic Stem Cell Transplant Recipients: A Systematic Review and Meta-Analysis

Abstract: This systematic review was undertaken to identify risk factors associated with post-transplant Epstein–Barr virus (EBV) active infection and post-transplant lymphoproliferative disease (PTLD) in pediatric and adult recipients of hematopoietic stem cell transplants (HSCT). A literature search was conducted in PubMed and EMBASE to identify studies published until 30 June 2020. Descriptive information was extracted for each individual study, and data were compiled for individual risk factors, including, when poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 109 publications
(338 reference statements)
0
7
0
Order By: Relevance
“…There is a paucity of studies addressing the risk of SNs after UCBT, and data related to SNs in long-term survivors after this procedure are scarce. Few observational studies 6 , 7 , 8 , 14 , 15 reported the occurrence of SNs after UCBT but the sample sizes were too narrow to allow risk comparison with transplants using adult donor grafts.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of studies addressing the risk of SNs after UCBT, and data related to SNs in long-term survivors after this procedure are scarce. Few observational studies 6 , 7 , 8 , 14 , 15 reported the occurrence of SNs after UCBT but the sample sizes were too narrow to allow risk comparison with transplants using adult donor grafts.…”
Section: Discussionmentioning
confidence: 99%
“…For many hematological diseases, allogeneic HSCT is the only curative therapeutic option 1,2 . Yet, this therapy is associated with high treatment complications, morbidity and mortality [10][11][12][13] . Several criteria were introduced in clinical practice to predict outcome after allogeneic HSCT to select and advise patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bonong et al found that the use of antithymocyte globulin in HSCT patients is an important risk factor for herpes infection after transplantation. 36 Beswick et al reported that chronic GVHD and cytomegaloviremia were significantly associated with nontuberculous mycobacterial diseases. 37 Likewise, we found that C 0 can be used to monitor the occurrence of adverse reactions as the level of C 0 significantly increases at the time of infection.…”
Section: Discussionmentioning
confidence: 99%